Free radical damage in stored plant germplasm - Benson, E.E. (1990)
IBPGR commissioned this report to examine the implications of free radical activity for the safe conservation of plant genetic resources. This report evaluates the role of free radical damage in plant germplasm stored either as a seed or as in vitro (tissue culture) systems under cryopreservation in liquid nitrogen.